Hizbut Tahrir's Political and Legal Movement in Indonesia During the Reformation Period - Amirullah, Amirullah; Rahmawati, Rahmawati (Civiliza Publishing, 2024)
This research tries to explain and describe the political movement of Hizbut Tahrir in Indonesia. By using qualitative methods through literature studies, this research produces the conclusion that Hizbut Tahrir Indonesia is one of the most solid, neat and efficient sharia enforcement movements. has an international network. In fact, Hizbut Tahrir Indonesia is also known to be the most radical, in the sense that it does not just fight upholding Islamic law but more than that also establishing an Islamic caliphate because according to Hizbut Tahrir Indonesia, the application of Islamic law is absolutely impossible applied except within the framework of the caliphate. One of the strategies used by Hizbut Tahrir Indonesia in spreading ideas, by controlling strategic arenas in the middle public.